Design and Implementation of A Monitoring System for Geological Archives - Sun Min (Universitas Ahmad Dahlan, 2015)
A monitoring system for geological archives with TCP/IP network communication is designed in this research to address wide distribution range, long distance, slow data updating, and difficult maintenance of city and county geological archives. The designed system uses the single chip STC11F32XE and the Ethernet control chip RTL8019AS as a hardware platform. The hardware design scheme, software design method, and the main programming flowchart of the geological archive monitoring unit were presented, and a specific data test was carried out. This monitoring system not only monitors and controls temperature, humidity, ponding, power supply, and other environmental data in geological archives, but also realizes geological data transmission between city (county) and provincial geological archives. In addition, this system is designed with a GSM warning mechanism, which could accelerate the quick response mechanism of the system. The entire monitoring system is accessed through the provincial environmental resources website with a fixed IP address. To ensure standardization of the monitoring system, the data transmission standard of the application layer used the associated standards of the Ministry of National Land and Resources. The entire system design improves the storage environment of the geological data effectively. It provides important data support to solve inconsistencies between provincial and city (county) geological data, as well as ensures scientific management of geological issues.